2014
DOI: 10.1016/j.amjoto.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Subspecialty emergency room as alternative model for otolaryngologic care: Implications for emergency health care delivery

Abstract: Purpose A dedicated otolaryngology emergency room (ER) represents a specialized surgical evaluation and treatment setting that may be an alternative triage pathway for acute otolaryngologic complaints. We aim to characterize practice patterns in this setting and to provide insight into the epidemiology of all-comer, urgent otolaryngologic complaints in the United States. Methods and Methods Electronic medical records were reviewed for all patients who registered for otolaryngologic care and received a diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Emergency department visits are a common route of hospital readmission. Postoperative complications are a frequent reason for otolaryngology patients to present to the emergency department . Young et al reviewed 30dEDRs in patients who underwent thyroidectomy or parathyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency department visits are a common route of hospital readmission. Postoperative complications are a frequent reason for otolaryngology patients to present to the emergency department . Young et al reviewed 30dEDRs in patients who underwent thyroidectomy or parathyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study was not geared to directly answer the question of access, patient presentation to the ED may to be related to patient education or difficulty obtaining immediate access to primary care providers, and significant research has addressed patient decision making for visiting the ED versus outpatient setting for other diagnoses . Prior studies evaluating dedicated otolaryngology and ophthalmology EDs have also demonstrated that the majority of problems evaluated in an “emergency” setting are actually not true emergencies, and these patients may place additional strain on the healthcare safety net . Moreover, as many otologic diagnoses are potentially due to an infectious etiology, there may be overuse (or incorrect use) of antibiotics …”
Section: Discussionmentioning
confidence: 99%
“…Although most otologic complaints do not require rapid evaluation and treatment, the concept of a regionalized system for triage of particular complaints may also be applied to more common diagnoses and provide an additional mechanism to decrease nonurgent complaints in EDs. Previous reports have demonstrated the potential for urgent care or retail clinics, or even subspecialty EDs adjacent to standard EDs that may be able to provide rapid access to specialists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, it has been estimated that diagnoses such as dizziness and vertigo and otitis media and eustachian tube disorders accounted for almost 4 million and 2 million ED visits, respectively . The overwhelming number of ENT‐related ED visits has spawned the creation of otolaryngology‐specific EDs to address this high demand for services . Although these appear to be a cost‐beneficial method for addressing acute ENT complaints, can offload a sizeable number of general ED visits, and even augment residency education, staffing is a potential challenge and they have not yet become commonplace .…”
Section: Introductionmentioning
confidence: 99%